The politics of Eurasianism identity, popular culture and Russia's foreign policy - Bassin, Mark; Pozo, Gonzalo (Rowman & Litlefield, 2017)
This collection explores Eurasianism and its interactions with and effects on political discourses, identity debates, and popular culture.